A salmonellosis case caused by Salmonella dublin in Turkey - Akman, Muvaffak; Aksoycan, Namık; Bertan, Münevver (The Turkish Journal of Pediatrics, 1961)
A case of salmonellosis in a six months old female infant, in which the organism isolated from blood culture proved to be Salmonella dublin, is reported. This is the first reported isolation of S. dublin from a human salmonellosis case in Turkey.